The importance of ultrasound of primagravidae’s thoughts about their unborn child - Dykes, K; Stjernqvist, Karin (Journal of Reproductive and Infant Psychology, 2001)
Evaluated the importance of ultrasound to women’s thoughts about their unborn child. 10 first-time mothers (ages 22 – 33 years) with normal pregnancies were interviewed approxi¬mately 1 week before and 1 week after their first ultrasound screening. Analysis of the interviews was conducted using the techniques of grounded theory. The results show that ultrasound was of great importance for increasing the women’s awareness of bearing a child. This realization process was expressed in various categories of thoughts about the unborn child: 1. The existing fetus, 2. The coming child, 3. The woman’s life situation, 4. Parenthood and 5. Delivery. The paper examined the way in which ultrasound influences these categories of thought.
Keywords: Developmental Psychology; Behavioral Medicine; Early Years - Education; Ethics & Legal issues in Mental Health; Health Psychology; Infancy; Nursing & Midwifery